Avaliação de resistência de cultivares de amendoim de hábito de crescimento rasteiro a Enneothrips flavens Moulton (Thysanoptera: Thripidae) - Boiça Junior, A.l. [UNESP]; Chagas Filho, N.r.; Godoy, I.j. De; Lourenção, A.l.; Souza, J.r. De [UNESP] (Instituto Biológico, 2012)
Due to its widespread distribution and known damages, Enneothrips flavens Moulton is considered the major pest of the peanut crop in Brazil. The objective of the present study was to evaluate the behavior of four runner peanut cultivars under natural field infestation of this insect. The experiments were carried out in the experimental area of FCAV/UNESP, Jaboticabal, state of São Paulo, Brazil, using a completely randomized block design with 4 treatments and 6 replications. The cultivars studied were IAC Caiapó, IAC 125, IAC 147 and Runner IAC 886. Insect infestation and damage, as well as plant behavior were evaluated as to the number of nymphae and adults, percentage of attacked leaflets, symptoms of attack intensity, number of apical buds/plant, plant dry weight, yield of unshelled pods/plant and 100 kernel weight. No significant difference was noted between cultivars regarding the level of E. flavens (adult and nymphae) infestation. The largest nymphae infestation was recorded at the 15-41 DAE (days after emergency) period. As for the adults, the largest infestation occurred between 15 and 48 days after emergence. The evaluation of yield performance under thrips (E. flavens) infestation suggested that the cultivar IAC Caiapó behaved as tolerant to the attack of this insect.

Devido a sua ampla distribuição e aos danos acarretados, Enneothrips flavens Moulton destaca-se como a principal praga do amendoim no Brasil. O objetivo do presente trabalho foi avaliar, em condições de campo, o comportamento de quatro cultivares de amendoim de hábito de crescimento rasteiro sob infestação natural de E. flavens. Os experimentos foram desenvolvidos na área experimental do Departamento de Fitossanidade da FCAV/UNESP - Campus de Jaboticabal, SP. O delineamento experimental utilizado foi em blocos ao acaso, com quatro tratamentos em seis repetições. Foram utilizadas os cultivares IAC Caiapó, IAC 125, IAC 147 e IAC Runner-886. Foram avaliados o número de ninfas e adultos de E. flavens, porcentagem de folíolos atacados, sintomas de intensidade de ataque, número de brotos apicais por planta, massa seca das plantas, produção de grãos em casca (kg ha-1) e a massa seca de 100 sementes (g). Os cultivares não diferiram quanto ao nível de infestação de ninfas e adultos de E. flavens. O período de maior infestação de ninfas ocorreu entre 15 e 41 DAE, e de adultos entre 15 e 48 DAE. Analisando-se a produção, o cultivar IAC Caiapó comportou-se como portador de resistência do tipo tolerância ao ataque de E. flavens.
Evaluation of peanut cultivars with runner growing habit for resistance to Enneothrips flavens, Moulton (Thysanoptera: Thripidae)
Keywords: Tripes; Arachis hypogaea; resistência de plantas a insetos; Thrips; Arachis hypogaea; host plant resistance